Low-Grade Clay as an Alkali-Activated Material - Muhammad M. Rahman; David W. Law; Indubhushan Patnaikuni; Chamila Gunasekara; Morteza Tahmasebi Yamchelou (Applied Sciences, 2021)
The potential application of alkali-activated material (AAM) as an alternative binder in concrete to reduce the environmental impact of cement production has now been established. However, as the production and availability of the primarily utilized waste materials, such as fly Ash and blast furnace slag, decrease, it is necessary to identify alternative materials. One such material is clay, which contains aluminosilicates and is abundantly available across the world. However, the reactivity of untreated low-grade clay can be low. Calcination can be used to activate clay, but this can consume significant energy. To address this issue, this paper reports the investigation of two calcination methodologies, utilizing low-temperature and high-temperature regimes of different durations, namely 24 h heating at 120 °C and 5 h at 750 °C and, and the results are compared with those of the mechanical performance of the AAM produced with untreated low-grade clay. The investigation used two alkali dosages, 10% and 15%, with an alkali modulus varying from 1.0 to 1.75. An increase in strength was observed with calcination of the clay at both 120 and 750 °C compared to untreated clay. Specimens with a dosage of 10% showed enhanced performance compared to those with 15%, with Alkali Modulus (AM) of 1.0 giving the optimal strength at 28 days for both dosages. The strengths achieved were in the range 10 to 20 MPa, suitable for use as concrete masonry brick. The conversion of Al (IV) is identified as the primary factor for the observed increase in strength.